IMU-based joint angle measurement for gait analysis - Seel, Thomas; Raisch, Joerg; Schauer, Thomas (Sensors, 2014)
This contribution is concerned with joint angle calculation based on inertial measurement data in the context of human motion analysis. Unlike most robotic devices, the human body lacks even surfaces and right angles. Therefore, we focus on methods that avoid assuming certain orientations in which the sensors are mounted with respect to the body segments. After a review of available methods that may cope with this challenge, we present a set of new methods for: (1) joint axis and position identification; and (2) flexion/extension joint angle measurement. In particular, we propose methods that use only gyroscopes and accelerometers and, therefore, do not rely on a homogeneous magnetic field. We provide results from gait trials of a transfemoral amputee in which we compare the inertial measurement unit (IMU)-based methods to an optical 3D motion capture system. Unlike most authors, we place the optical markers on anatomical landmarks instead of attaching them to the IMUs. Root mean square errors of the knee flexion/extension angles are found to be less than 1° on the prosthesis and about 3° on the human leg. For the plantar/dorsiflexion of the ankle, both deviations are about 1°. © 2014 by the authors; licensee MDPI, Basel, Switzerland.
CRIS-Team Scopus Importer:2021-03-31
Keywords: Avoid magnetometers; Exploit kinematic constraints; Gait analysis; Gyroscopes and accelerometers; Inertial measurement units; Joint angle measurement; Joint axis and position identification; Sensor-to-segment mounting; Validation against optical gait analysis; Validation on prosthetic and human leg